Numerical Simulation of 1-D and 2-D Continuous Geo-electrical Magnetotelluric Forward - Cao Chuang Hua; Liu Jian Xin; Tong Xiao Zhong; Gao Da Wei (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Finite element technology in one-dimensional layered media of the continuous electro-media and the two-dimensional continuous electrical is displayed in ways of the special matrix equations in the variation formula and split technical conditions. To achieve a one-dimensional layered continuous electrical finite element numerical simulation of the media, the introduction of the secondary triangulation rectangular subdivision has been used to the two-dimensional numerical simulation, and using the rectangular center to set up the virtual point method to reduce the computational workload in calculation. Then design a meaningful manner electric model, the base power model analysis of electromagnetic waves in the rock, they all provide the guidance for the actual production. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2717